The Effects of Sundanese Kacapi Suling “Ayun Ambing” Music Therapy to The Level of Anxiety on Chronic Renal Failure Patient Undergoing Hemodialysis - Mustopa Saepul Alamsah; Laili Rahayuwati; Chandra Isabella Hostanida Purba (Faculty of Nursing Universitas Padjadjaran, 2018)
ABSTRACT One of the most common psychological problems found in patients with chronic renal failure (ESRD) undergoing hemodialysis is anxiety. Unresolved anxiety can have a negative impact on physiological and psychological conditions that can aggravate the condition of the disease. Traditional Sundanese music therapy Kacapi Suling